Grundsätze ordnungsgemäßer Bewertung durch Scoring - Andreas Oehler (Wirtschaftsdienst, 2017)
Die digitale Durchleuchtung und Bewertung des Verhaltens von Konsumenten und Bürgern nach einem Punktesystem (Scoring) ist in repressiven Staaten wie China schon weit gediehen. Aber auch in Deutschland werden mit diesem System Bürger als Verbraucher in der Finanzwirtschaft oder als Patienten im Bereich Gesundheitsversorgung und Versicherungen bewertet. Die Problematik wird in der Öffentlichkeit wenig diskutiert. Dies überrascht insofern, als nahezu jede und jeder betroffen ist und zukünftig noch stärker als bisher im Rahmen der voranschreitenden Digitalisierung eingebunden sein dürfte. – – Scoring and comparable methods that are used to rate people's future behaviour can provide useful information for suppliers and thereby reduce the asymmetrical information deficits and the corresponding risks (screening). Likewise, consumers can profit from scoring if they use the scores to reveal their creditworthiness (signalling). In a market economy where markets are not fully transparent, scoring agencies act as information intermediaries. They provide information on future behaviour at the meta level so that not every supplier or consumer has to rate themselves. This is why the reliability of scores and scoring agencies is so fundamental. This article examines the principles or minimum standards for valid scoring and discusses how to introduce, regulate and test them.
Keywords: D11; D18; K2; 330